Paper-based microfluidic aptasensors - Ming, Tao; Luo, Jinping; Liu, Juntao; Sun, Shuai; Xing, Yu; Wang, Hao; Xiao, Guihua; Deng, Yu; Cheng, Yan; Yang, Zhugen; Jin, Hongyan; Cai, Xinxia (Elsevier, 2020)
For in-situ disease markers detection, point-of-care (POC) diagnosis has great advantages in speed and cost compared with traditional techniques. The rapid diagnosis, prognosis, and surveillance of diseases can significantly reduce disease-related mortality and trauma. Therefore, increasing attention has been paid to the POC diagnosis devices due to their excellent diagnosis speed and portability. Over the past ten years, paper-based microfluidic aptasensors have emerged as a class of critical POC diagnosis devices and various aptasensors have been proposed to detect various disease markers. However, most aptasensors need further improvement before they can actually enter the market and be widely used. There is thus an urgent need to sort out the key points of preparing the aptasensors and the direction that needs to be invested in. This review summarizes the representative articles in the development of paper-based microfluidic aptasensors. These works can be divided into paper-based optical aptasensors and paper-based electrochemical aptasensors according to their output signals. Significant focus is applied to these works according to the following three parts: (1) The ingenious design of device structure; (2) Application and synthesis of nanomaterial; (3) The detection principle of the proposed aptasensor. This is a detailed and comprehensive review of paper-based microfluidic aptasensors. The accomplishments and shortcomings of the current aptasensors are outlined, the development direction and the future prospective are given. It is hoped that the research in this review can provide a reference for further development of more advanced, more effective paper-based microfluidic aptasensors for POC disease markers diagnosis
Keywords: Point-of-care Diagnosis; Nanomaterial; Portable equipment; Point-of-care Diagnosis; Microfluidic chip; Paper-based device; Aptasensor